2015
DOI: 10.1017/s147474561500052x
|View full text |Cite
|
Sign up to set email alerts
|

Trade Costs in the Developing World: 1996–2010

Abstract: We use new data on trade and production in 167 countries to infer estimates of trade costs for manufactured goods and agriculture for 1996‒2010. Trade costs are strongly declining in country income level. Among developing countries, only the upper middle income group has been successful in reducing trade costs faster than elsewhere in the world. Sub-Saharan African countries and low income countries remain subject to very high trade costs. Regional trade agreements, maritime transport connectivity, and trade f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 22 publications
1
130
0
4
Order By: Relevance
“…Anderson and Van Wincoop (2004) combine estimates from the literature to suggest that a representative developed economy has trade costs of over 70%, even though applied tariff rates are typically under 5%. Subsequent work by Arvis et al (2016) showed that when estimated rigorously using an inversion of the standard gravity model, trade costs in the developing world can be even higher: over 100% in many cases, and double that again in agriculture. Again, trade costs are a clear order of magnitude larger than applied rates of tariff protection, which means that policy makers are frequently surprised by the results from studies like Arvis et al (2016) even though they show movement in a positive directionfalling trade costs, at least in manufacturing-over recent decades.…”
Section: "Broad Sense" Trade Facilitation: Lowering Trade Costsmentioning
confidence: 99%
“…Anderson and Van Wincoop (2004) combine estimates from the literature to suggest that a representative developed economy has trade costs of over 70%, even though applied tariff rates are typically under 5%. Subsequent work by Arvis et al (2016) showed that when estimated rigorously using an inversion of the standard gravity model, trade costs in the developing world can be even higher: over 100% in many cases, and double that again in agriculture. Again, trade costs are a clear order of magnitude larger than applied rates of tariff protection, which means that policy makers are frequently surprised by the results from studies like Arvis et al (2016) even though they show movement in a positive directionfalling trade costs, at least in manufacturing-over recent decades.…”
Section: "Broad Sense" Trade Facilitation: Lowering Trade Costsmentioning
confidence: 99%
“…On the basis of these findings, she argues that services market opening should be considered as an element of strategies for industrial upgrading in developing countries. Miroudot and Shepherd (2015) find that a 10 per cent increase in the level of services trade restrictiveness is associated with an increase in trade costs of 2.7-3.1 per cent, using trade costs data compiled by Arvis et al (2015), the biggest effects being in postal services and telecommunications. Borchert et al (2015) note that many landlocked African countries restrict trade in services that could have a significant effect on overall trade performance; for example, air transport policies tend to be significantly more restrictive than in other countries, reducing connectivity with the rest of the world.…”
Section: Services Trade Policies and Economic Performancementioning
confidence: 99%
“…A fuller picture, however, emerges from the World Bank's bilateral trade cost data set that provides such an aggregate measure. This indicator measures total trade costs in terms of the trade‐depressing effect of national borders relative to domestic costs (Arvis et al., ).…”
Section: Nature and Drivers Of Trade Costsmentioning
confidence: 99%
“…Indeed, one of the authors of this paper might himself be criticised with hindsight for investigating the incentive effects of only traditional border measures for Madagascar itself in the 1980s (Greenaway and Milner, ). We now have much evidence and research on the nature, determinants and extent of trade costs broadly defined (Milner, ; Anderson and van Wincoop, ; Arvis et al., ). So whereas the Madagascar TPR (WTO, ) reports that the average, applied tariff on Madagascar's imports is 12.2 per cent, we know from the UNESCAP‐World Bank Trade Cost Database that Madagascar's (average) bilateral trade costs with its actual trade partners are still in excess of 300 per cent ad valorem.…”
Section: Introduction and Contextmentioning
confidence: 99%